Mandatory surveillance and outbreaks reporting of the WHO priority pathogens for research & discovery of new antibiotics in European countries. (July 2020) - Babu Rajendran, N.; Mutters, N.T.; Marasca, G.; Conti, M.; Sifakis, F.; Vuong, C.; Voss, A.; Baño, J.R.; Tacconelli, E.
Abstract: Objectives: In 2017 the WHO published a global priority list of 12 antibiotic-resistant bacteria (ARB) in urgent need of new antibiotics. We aimed to identify and assess publicly accessible mandatory surveillance systems and outbreaks reporting for these pathogens in the 28 European Union and four European Free Trade Association member states. Methods: Compulsory reporting was mapped by reviewing national documents without applying language restrictions and through expert consultation. Information on surveillance targets, indicators, metrics and dissemination modalities was extracted and a qualitative assessment was performed for open access systems only. Results: Twenty-one countries (66%) had a mandate to survey at least one among the 12 WHO priority pathogens; 15 provided access to surveillance frameworks. These systems covered most frequently carbapenem-resistant Enterobacteriales (12; 38%), methicillin-resistant Staphylococcus aureus (12; 38%), and vancomycin-resistant enterococci (8; 25%). None of the European countries required reporting of resistance in Salmonella, Campylobacter, Helicobacter pylori and Neisseria gonorrhoeae. High heterogeneity was observed in data collection, reporting and dissemination among countries with clinical outcomes and risk factors being reported in less than half (22% and 25%). Only six countries (19%) implemented mandatory surveillance of outbreaks due to at least one WHO priority pathogen. Conclusions: Our review shows that despite the increasing burden of ARB on the European population, very few countries implemented mandatory surveillance and outbreak reporting of the WHO priority pathogens. International efforts are needed to define the effectiveness of implementing mandatory reporting of these pathogens and to assess their role in reducing the spread of ARB in health-care and community settings.